Collage and architecture - Shields, Jennifer A. E. (New York ; $a London Routledge, Taylor and Francis Group, 2024)
"Collage and Architecture remains an invaluable resource for students and practitioners as the first book to cover collage as a tool for analysis and design in architecture. Since entering the contemporary art world over a century ago, collage has profoundly influenced artists and architects throughout the twentieth century and into the twenty-first. In Collage and Architecture, Jennifer A.E. Shields explores its influence, using the artworks and built projects of leading artists and architects, such as Mies van der Rohe, Daniel Libeskind, and Teddy Cruz to illustrate the diversity of collage techniques. This new edition includes: A stronger focus on contemporary practices, including digital methods New designers and architects, including Marshall Brown, WAI Architecture Think Tank, and Tatiana Bilbao, bringing their methods and work to life An expanded global and diverse perspective of architecture as collage Collage is an important instrument for analysis and design. Through its 290 color images, this book shows how this versatile medium can be adapted and transformed in your own work"--
Includes bibliographical references and index.
Keywords: Architectural design -- Methodology; Collage